Layer‐by‐Layer Processed Ternary Organic Photovoltaics with Efficiency over 18%. Issue 12 (18th February 2021) - Zhan, Lingling; Li, Shuixing; Xia, Xinxin; Li, Yaokai; Lu, Xinhui; Zuo, Lijian; Shi, Minmin; Chen, Hongzheng
Abstract: Obtaining a finely tuned morphology of the active layer to facilitate both charge generation and charge extraction has long been the goal in the field of organic photovoltaics (OPVs). Here, a solution to resolve the above challenge via synergistically combining the layer‐by‐layer (LbL) procedure and the ternary strategy is proposed and demonstrated. By adding an asymmetric electron acceptor, BTP‐S2, with lower miscibility to the binary donor:acceptor host of PM6:BO‐4Cl, vertical phase distribution can be formed with donor‐enrichment at the anode and acceptor‐enrichment at the cathode in OPV devices during the LbL processing. In contrast, LbL‐type binary OPVs based on PM6:BO‐4Cl still show bulk‐heterojunction like morphology. The formation of the vertical phase distribution can not only reduce charge recombination but also promote charge collection, thus enhancing the photocurrent and fill factor in LbL‐type ternary OPVs. Consequently, LbL‐type ternary OPVs exhibit the best efficiency of 18.16% (certified: 17.8%), which is among the highest values reported to date for OPVs. The work provides a facile and effective approach for achieving high‐efficiency OPVs with expected morphologies, and demonstrates the LbL‐type ternary strategy as being a promising procedure in fabricating OPV devices from the present laboratory study to future industrial production. Abstract : Combining the layer‐by‐layer processing method and a ternary strategy, 18.16% efficiency, which is among the highest values reported to date, is achieved in single‐junction organic photovoltaics (OPVs) based on the PM6:BO‐4Cl:BTP‐S2 blend, superior to that (18.03%) of bulk‐heterojunction OPVs, proving that layer‐by‐layer processed ternary OPVs could be a promising approach to high efficiencies.